The Influence Of Product Innovation And Image On The Purchase Decision Of Hijab Products Trought Purchase Intention - Puteri Adinda Sari; Rosana Eri P Puspita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aims to analyze and determine the influence of Product Innovation and brand image on purchasing decisions, with purchase interest as an intervening variable. This study used quantitative research with primary data types and non-probability sampling techniques with as many as 75 sample respondents. Data was collected through questionnaires and processed using testing with SPSS version 20. The results of this study are that Product Innovation and brand image do not affect purchasing decisions, buying Interest has a positive effect on purchasing decisions, Product Innovation and brand image have a positive impact on buying Interest, buying Interest can mediate Product Innovation on purchasing decisions, but buying Interest cannot mediate Brand image of purchasing decisions.Keywords: Brand Image, Purchasing Decision, Buying Interest, Product Innovation